Fractal patterns in nonlinear dynamics and applications - Banerjee, Santo; Hasan, M K.; Mukherjee, Sayan; Gowrisankar, A. (Boca Raton : CRC Press, 2020)
"Most books on fractals, focus on deterministic fractals as the impact of incorporating randomness and time is almost absent. Further, most review fractals without explaining what scaling and self-similarity means. This book introduces the idea of scaling, self-similarity, scale-invariance and their role in the dimensional analysis. For the first time, fractals emphasizing mostly on stochastic fractal, and multifractals which evolves with time instead of scale-free self-similarity, are discussed. Moreover, it looks at power laws and dynamic scaling laws in some detail and provides an overview of modern statistical tools for calculating fractal dimension and multifractal spectrum"--
Includes bibliographical references and index.
Keywords: Fractals